Filipino attitudes toward lesbians and gay men; Secondary Analysis of 1996 and 2001 National Survey Data. [article]. - Manalastas, Eric Julian
Using data from national survey conducted by the Social weather Station in 1996 and in 2001 (n=1,200), we examined the attitudes of Filipinos as a general population toward lesbians and gay men. Secondary analysis of two heterosexism measures included in the surveys indicated that Filipinos held largely negative attitudes towards lesbians and gay men. Many Filipinos (about 28 %) considered being gay/lesbian as "can never be justified." while only 4% thought it could "always be justified." In addition, about 1 out of 4 Filipinos expressed not wanting gay men/lesbians as neighbors. These heterosexist views did not change significantly from 1996 to 2001 and were widespread, regardless of gender, socio-economic status, educational attainment. or religiosity. Respondents from NCR had the least negative evaluations, and attitudes towards lesbians and gay men were positively correlated to attitudes toward sex work, abortion, and divorce.